Gerai Kopi di Jakarta dalam Adaptasi Kehidupan Baru - Pandu Adi Cakranegara (Samarinda State Polytechnic, 2020)
Covid 19 pandemic in Jakarta forced individuals living in Jakarta to live New Normal. Restaurants, food stalls and various eating places were hit hard by this situation. This study tries to look at the impact of Covid 19 and what cafe owners are doing to be able to adapt in the New Life Adaptation Era. The method used was observation and interviews with 50 coffee cafes in various regions in Jakarta. From the results of interviews and observations there are several things that can be concluded. Coffee shops need to take new and unusual steps before the pandemic in order to survive. The steps found in this research are to build personal relationships with customers, cost savings, and focus on online marketing.